Post‐Assembly Modification of Homochiral Titanium–Organic Cages for Recognition and Separation of Molecular Isomers - Chen, Guang‐Hui; He, Yan‐Ping; Yu, Yinghua; Lv, Hong; Li, Shangda; Wang, Fei; Gu, Zhi‐Gang; Zhang, Jian (Angewandte Chemie International Edition, 2023)
A chiral metal–organic cage (MOC) was extended and fixed into a porous framework using a post‐assembly modification strategy, which made it easier to study the host–guest chemistry of the solid‐state MOC using a single‐crystal diffraction technique. Anionic Ti4L6 (L=embonate) cage can be used as a 4‐connecting crystal engineering tecton, and its optical resolution was achieved, thus homochiral ΔΔΔΔ‐ and ΛΛΛΛ‐[Ti4L6] cages were obtained. Accordingly, a pair of homochiral cage‐based microporous frameworks (PTC‐236(Δ) and PTC‐236(Λ)) were easily prepared by a post‐assembly reaction. PTC‐236 has rich recognition sites provided by the Ti4L6 moieties, chiral channels and high framework stability, affording a single‐crystal‐to‐single‐crystal transformation for guest structure analyses. Thus it was successfully utilized for the recognition and separation of isomeric molecules. This study provides a new approach for the orderly combination of well‐defined MOCs into functional porous frameworks. A chiral metal–organic cage has been extended and introduced into a porous framework by using a post‐assembly modification strategy. The microporous frameworks were successfully utilized for the recognition and separation of isomeric molecules, including aromatic compounds, nitriles, and chiral aromatic alcohols.